2019
DOI: 10.1182/bloodadvances.2019000480
|View full text |Cite
|
Sign up to set email alerts
|

Similar outcomes of alemtuzumab-based hematopoietic cell transplantation for SAA patients older or younger than 50 years

Abstract: Key Points GRFS is similar between older and younger patients using FCC conditioning but comorbidities impact on outcome of SAA HSCT. Immunomodulatory B lymphocytes potentially contribute to control of alloreactivity and low GVHD after FCC HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…With improved survival after HSCT, the upper age limit for up-front MSD HSCT has steadily increased, according to comorbidities and fitness for HSCT. 68,[71][72][73][74][75] Up-front matched unrelated donor (MUD) HSCT may be considered as an option for young adults with SAA/VSAA who lack a MSD, who urgently need a transplant to achieve early neutrophil engraftment on account of severe/life-threatening sepsis, and where multiple MUDs are readily available and one is recruited to donate in a very short time frame. This reflects a similar approach in children, [76][77][78] although randomised controlled trials comparing IST with MUD are not yet available.…”
Section: Fir St-li N E Tr E Atm E N T Of Acqu Ir E D a Amentioning
confidence: 99%
See 1 more Smart Citation
“…With improved survival after HSCT, the upper age limit for up-front MSD HSCT has steadily increased, according to comorbidities and fitness for HSCT. 68,[71][72][73][74][75] Up-front matched unrelated donor (MUD) HSCT may be considered as an option for young adults with SAA/VSAA who lack a MSD, who urgently need a transplant to achieve early neutrophil engraftment on account of severe/life-threatening sepsis, and where multiple MUDs are readily available and one is recruited to donate in a very short time frame. This reflects a similar approach in children, [76][77][78] although randomised controlled trials comparing IST with MUD are not yet available.…”
Section: Fir St-li N E Tr E Atm E N T Of Acqu Ir E D a Amentioning
confidence: 99%
“…Outcomes in older patients, including those over 70 years, have improved, 72,74,122 but the presence of comorbidities impacts on outcome. A conditioning protocol that minimises GVHD is advocated.…”
Section: Syngeneic Donormentioning
confidence: 99%
“…An age cut‐off of 40 has been applied given the higher transplant mortality in patients over this age 97,105–107 . Some centres extend to age 50 in very selected cases when comorbidities and performance status are not limiting 108,109 . Nonetheless, most AA patients worldwide receive a non‐transplant treatment modality given age, comorbidities, lack of a suitable donor, lack of access to transplant, or patient’s choice.…”
Section: Therapymentioning
confidence: 99%
“…97,[105][106][107] Some centres extend to age 50 in very selected cases when comorbidities and performance status are not limiting. 108,109 Nonetheless, most AA patients worldwide receive a nontransplant treatment modality given age, comorbidities, lack of a suitable donor, lack of access to transplant, or patient's choice. Some have advocated for a MUD HSCT upfront in younger patients.…”
Section: Therapymentioning
confidence: 99%
“… 54 The most frequently used unrelated HCT regimens for AA patients, either fludarabine, ATG, cyclophosphamide and 2 Gy TBI or fludarabine combined with Campath antibody, appeared to produce similar results, including for older patients. 121 , 122 Moreover, recent papers reported outstanding survival figures for AA patients given HLA-haploidentical grafts. 123 , 124 Taken together, these findings suggested that upfront marrow transplantation should be considered for all patients with AA who have a suitable donor rather than waiting until failure of immunosuppressive therapy.…”
Section: Current Trendsmentioning
confidence: 99%